Economic Scientific Quality as The Knowledge Assessment of Human Capital Productivity at The Enterprise (Economics and region, 2018)
The issues of the influence of knowledge on the productivity of labor of the enterprise’s human capital are considered. The necessity of applying the new indicator "economic science intensity" for determining the level of use of knowledge at the enterprise, the potential of knowledge of the enterprise and determining ways to increase labor productivity by raising the potential of knowledge is substantiated. A structural analysis of the organization of the enterprise is carried out. There are identified the departments that are most connected with the use and accumulation of knowledge. The rationale for choosing the factors that affect the indicator "economic science" is presented.
Keywords: knowledge economy; labor productivity; human capital; intellectual labor; new technologies; intellectual property